Liquidity and Asset Growth on Telecommunications Companies Value - Nardi Sunardi (Jurnal SEKURITAS (Saham, Ekonomi, Keuangan dan Investasi), 2022)
The purpose of this study was to determine the effect of liquidity as proxied by Current Ratio (CR) and Asset Growth as proxied by Asset Growth Ratio (AGR) to firm value (PBV) in telecommunications companies. The type of data used in this research is secondary data. The sampling technique used in this research is purposive sampling. The population are telecommunication companies listed on the Indonesia Stock Exchange as many as 3 telecommunication companies in the 2016-2021 period. The research method is descriptive with a quantitative approach, namely the data obtained and analyzed on the basis of numbers that exist in telecommunications companies listed on the Indonesia Stock Exchange in 2016-2021, the research method is panel data regression analysis. Based on the results of the research hypothesis t test shows that liquidity has a significant effect on firm value and firm growth has no significant effect on firm value. Then, liquidity and firm simultaneously or jointly have a significant effect on firm value.